KERJASAMA TEKNIK INDONESIA INDONESIA – MELANESIAN SPEARHEAD GROUP TERHADAP KEUTUHAN NKRI di PAPUA TAHUN 2011-2014 - Lia Kartika Tampubolon (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research to describe why Indonesia establish technical cooperation with the Melanesian Spearhead Group. Members of Melanesian Spearhead Group is the state of race melanesia. Vision owned by the Melanesian Spearhead Group is decolonization and freedom throughout the country Melanesia. West Papua National Coalition for Liberation register as a member of the Melanesian Spearhead Group. Indonesia tried to prevent Papua be a member of the Melanesian Spearhead Group with establish technical cooperation. Directorate of Technical Cooperation divides its activities into two types; operations and activities within the framework of strengthening cooperation. The Future of Indonesian technical cooperation will depend on such things as the availability of budget, human resources and institutional. In fact, the budget for technical cooperation in the years reduced.The perspective of realism is used to support this research. Realism introduced by Hans J. Morgenthau. Realism have an approach to realize and understand the aspects that determine the political relations among nations, and t explain the ways of these aspects relate to each other and in international political relations. This research also used theory of cooperation because Indonesia establish techincal cooperation with Melanesian Spearhead Group.The main reason why Indonesia establish technical cooperation with the Melanesian Spearhead Group is because Indonesia wants the support of the Melanesian Spearhead Group and prevent Papua to be a member of Melanesian Spearhead Group. So that, Indonesia can maintain territorial sovereignty.Keywords: technical cooperation, support, Melanesian Spearhead Group, West Papua National Coalition for Liberation